Pemanfaatan Lahan Pekarangan Masyarakat Padukuhan Beneran Melalui Budidaya Tanaman Sayuran dalam Pot - Nanik Prasetyoningsih; Mujiyana Mujiyana; Lis Noer Aini; Nur Fadilah Al Idrus; Gunawan Wibisono; Kelik Iswandi (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The Community Service Program was implemented with partners of the governments of Padukuhan Beneran, Purwobinangun, Pakem and the Students Community Service Program. The Community Service Program Team assisted the Padukuhan Beneran community in utilizing their yard for planting vegetables in pots. This is done to achieve food security in the form of the community being in a position where food needs for their households are adequately met. The goal of this Community Service Program is to encourage the community to make good use of their yards in order to maintain family food self-sufficiency. Yard land utilization is a strategy for increasing food independence because yard land has the potential to provide family food. This Service Program consists of three activities: counseling on community food security, counseling on the use of yard land for vegetable cultivation, and training on planting vegetables in pots.